Characterization of the mature cell surface proteinase of Lactobacillus delbrueckii subsp. lactis CRL 581 - Villegas, Josefina Maria (2015)
The cell envelope-associated proteinase (CEP) of Lactobacillus delbrueckii subsp. lactis CRL 581 (PrtL) has an essential role in bacterial growth, contributes to the flavor and texture development of fermented products, and can release bioactive health-beneficial peptides during milk fermentation. The genome of L. delbrueckii subsp. lactis CRL 581 possesses only one gene that encodes PrtL, which consists of 1924 amino acids and is a multidomain protein anchored to the cell via its W domain. PrtL was extracted from the cell under high ionic strength conditions using NaCl, suggesting an electrostatic interaction between the proteinase and the cell envelope. The released PrtL was purified and biochemically characterized; its activity was maximal at temperatures between 37 and 40 °C and at pH between 7 and 8. Under optimal conditions, PrtL exhibited higher affinity for succinyl-alanyl-alanyl-prolyl-phenylalanine-p-nitroanilide than for succinyl-alanyl-glutamyl-prolyl-phenylalanine-p-nitroanilide, while methoxy-succinyl-arginyl-prolyl-tyrosyl-p-nitroanilide was not degraded. A similar α- and β-casein degradation pattern was observed with the purified and the cell envelope-bound proteinase. Finally, on the basis of its specificity towards caseins and the unique combination of amino acids at residues thought to be involved in substrate specificity, PrtL can be classified as a representative of a new group of CEP.